Ethnolinguistic Narratives of Latinidad: Radical Language-Mixing, Nostalgia, and Hybridity in Chávez Silverman’s Killer Crónicas - Pawelek, Lukasz D.; Derrick, Roshawnda A. (Nueva Revista del Pacífico, 2018)
Abstract:Spanish-English bilingual texts are mainly written in English and include some Spanish words to reference Hispanic culture and language. More recently, however, authors like Susana Chávez Silverman have been using a more sustained type of language mixing to narrate their multilingual, multi-geographical stories. In fact, Chávez Silverman to date is the only U.S. Hispanic author to publish a fully bilingual text, which uses sustained Spanish-English code-switching in the entire manuscript. In this context, the present article examines entries from Killer Crónicas (2004) with an interest in the nostalgic recall of Chávez Silverman. In order to carry out this study, we first conceptualize the notion of nostalgia using Boym’s (2001) framework to define this phenomenon as a syndrome of globalization and a catalyst that encourages Chávez Silverman to reevaluate her diverse multicultural experiences and evolving Latina identity through the implementation of geographical, cultural, literary as well as linguistic spaces. Further, we show how Chávez Silverman uses a hybrid mixture of Spanish and English to connect to scents, places and languages. This paper seeks to expand critical and analytical frontiers of understanding the Latino/a migratory experience and hybrid identity formation. Thus, in this regard, nostalgia emerges as a catalyst and analytic tool progressing from socio-geographical and linguistic reconfigurations, as well as modernization.Keywords: Nostalgia, Code-switching, Spanish in the USA, Crónica, Susana Chávez SilvermanResumen:Los textos latinos y bilingües de los Estados Unidos típicamente se escriben en inglés e incluyen algunos términos en español para referirse a la cultura y el lenguaje de los hispano-estadounidenses. Recientemente, autores como Susana Chávez Silverman han empezado a utilizar estrategias más radicales para mezclar los dos idiomas. Ello con la intención de narrar sus multi-geográficas y multilingües historias. De hecho, Chávez Silverman, hasta ahora, es la única latina-estadounidense que ha publicado un manuscrito que usa el cambio de código español-inglés a lo largo del texto. Por lo tanto, este artículo analiza corpus de Killer Crónicas (2004) con interés en la memoria nostálgica de Chávez Silverman. Para realizar este estudio, primero, conceptualizamos la noción de nostalgia utilizando la teoría de Boym (2001) para definir este fenómeno como un síndrome de la globalización, así como un catalizador que anima a Chávez Silverman a reevaluar sus diversas y multiculturales experiencias y su identidad latina. Una identidad en constante evolución por medio de los espacios geográficos, culturales, literarios y lingüísticos. Además, hacemos énfasis en cómo Chávez Silverman usa una mezcla híbrida del español e inglés para conectarse con los olores, lugares y lenguajes. Este artículo intenta ampliar las fronteras críticas y analíticas del entendimiento de la experiencia migratoria de los latinos y la formación de una identidad híbrida. En este contexto, la nostalgia funciona como un catalizador y un instrumento de análisis que surge de las reconfiguraciones socio-geográficas y lingüísticas, así como de la modernización.Palabras Clave: la nostalgia, el cambio de código, el español estadounidense, la crónica, Susana Chávez Silverman.